2022
DOI: 10.1097/aco.0000000000001170
|View full text |Cite
|
Sign up to set email alerts
|

Regional versus general anesthesia for ambulatory total hip and knee arthroplasty

Abstract: Purpose of reviewWith the removal of both total knee and total hip arthroplasty from the Centers for Medicare and Medicaid Services' inpatient-only list, efforts to improve efficiency of the perioperative management of total joint patients have increased recently. The publication of several recent studies examining the impact of anesthesia type on outcomes has prompted the need to review the overall state of evidence for spinal versus general anesthesia for outpatient total joint arthroplasty. Recent findingsO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…only procedure by Medicare/Medicaid, the duration of LOS -a factor representing both clinical outcomes and significant cost to the healthcare system -is an important consideration [23]. Outpatient TJAs have been found to have both lower complication rates and increased cost savings when compared to inpatient TJAs [24].…”
Section: Financial Supportmentioning
confidence: 99%
“…only procedure by Medicare/Medicaid, the duration of LOS -a factor representing both clinical outcomes and significant cost to the healthcare system -is an important consideration [23]. Outpatient TJAs have been found to have both lower complication rates and increased cost savings when compared to inpatient TJAs [24].…”
Section: Financial Supportmentioning
confidence: 99%
“…Although there are some absolute contraindictions to SA (patient refusal, spinal pathology, coagulopathy, etc. ), much of the choice between GA and SA often comes down to provider preference in the absence of contraindications [1]. While some studies have demonstrated decreased postoperative complications using SA [2][3][4], others have shown it to be non-superior to modern GA techniques even for rapid recovery [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Although the best choice of anaesthesia technique for major orthopaedic surgery is a matter of debate, spinal anaesthesia is an established component of perioperative management for fast-track lower limb arthroplasty [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%